Self-reported psychopathy and aggression motivation: a role for emotions?. Issue 1 (2nd January 2020) - Ireland, Jane L.; Lewis, Michael; Ireland, Carol A; Derefaka, Gail; Taylor, Louise; McBoyle, Joanne; Smillie, Louise; Chu, Simon; Archer, John
ABSTRACT: The current study examined the psychopathy-aggression relationship by considering different forms of aggression, including aggressive motivation. Emotions were explored as useful in understanding any emerging relationship, notably those consistent with detachment and sensitivity/poor regulation. In three studies, involving non-offending samples (Study one: n = 150, 47 men, 103 women; Study two: n = 442, 314 men, 123 women, five not disclosed; Study three: n = 200, 100 men and 100 women), it was predicted that higher levels of psychopathy would be associated with reports of higher overall, proactive and reactive aggression, and that the association would be moderated by emotion. Specifically, it was predicted that emotion regulation difficulties would associate with higher levels of reactive but not proactive aggression, and that proactive aggression would involve a lack of emotion. Findings generally supported the predictions. The role of emotion-regulation difficulties as a mediator between psychopathy and reactive aggression, and greater emotional detachment as a mediator between psychopathy and proactive aggression was demonstrated. The results demonstrate importance for the components of psychopathy and different aspects of emotion for the psychopathy-aggression link. Directions for future research and some implications for practice are outlined.